A Non-linear Resonator for Sensing Applications - Deng, C; Turnbull, R; Anthony, C; Ward, M; Collins, S (2010)
Their small mass means that the resonant frequency of Microelectromechanical (MEMs) resonators is sensitive to the absorption of a small additional mass onto their surface. Any change in resonant frequency caused by this additional mass can be detected by monitoring the amplitude or phase of a resonators response at a specific frequency. This means that the very sudden change in the amplitude and phase of a Duffing resonator at two critical frequencies is a phenomenon that could be exploited in this type of sensor. In this paper results are presented which show that a MEMs resonator can be made to act as a Duffing resonator using electronic feedback. The result is the basis for a new method of increasing the sensitivity of resonant sensors operating in air.